2022
DOI: 10.1002/aenm.202103939
|View full text |Cite
|
Sign up to set email alerts
|

Hysteresis‐Suppressed Reversible Oxygen‐Redox Cathodes for Sodium‐Ion Batteries

Abstract: Oxygen‐redox‐based cathode materials for sodium‐ion batteries (SIBs) have attracted considerable attention in recent years owing to the possibility of delivering additional capacity in the high‐voltage region. However, they still suffer from not only fast capacity fading but also poor rate capability. Herein, P2‐Na0.75[Li0.15Ni0.15Mn0.7]O2 is introduced, an oxygen‐redox‐based layered oxide cathode material for SIBs. The effect of Ni doping on the electrochemical performance is investigated by comparison with N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(44 citation statements)
references
References 64 publications
(127 reference statements)
1
34
1
Order By: Relevance
“…Relying on the unique advantages of high intensity, continuous wavelength tuning, and high resolution of synchrotron light sources, XAS has become one of the powerful tools for studying the structure of materials. It can be applied to study the chemical environment around the atoms of various elements in electrode materials and to obtain important information about the oxidation state, local structure, and proximity of coordination atoms of the constituent elements in electrode materials 45,77–80 . According to the energy range of X‐ray photons, they can be divided into soft XAS (sXAS) and hard XAS (hXAS), where sXAS tests X‐ray photons with low energy and weak penetration and can be used to study the energy state of superficial elements (K‐plane of C, O, N, etc.…”
Section: Charge Compensation Mechanism and Its Related Characterizati...mentioning
confidence: 99%
See 1 more Smart Citation
“…Relying on the unique advantages of high intensity, continuous wavelength tuning, and high resolution of synchrotron light sources, XAS has become one of the powerful tools for studying the structure of materials. It can be applied to study the chemical environment around the atoms of various elements in electrode materials and to obtain important information about the oxidation state, local structure, and proximity of coordination atoms of the constituent elements in electrode materials 45,77–80 . According to the energy range of X‐ray photons, they can be divided into soft XAS (sXAS) and hard XAS (hXAS), where sXAS tests X‐ray photons with low energy and weak penetration and can be used to study the energy state of superficial elements (K‐plane of C, O, N, etc.…”
Section: Charge Compensation Mechanism and Its Related Characterizati...mentioning
confidence: 99%
“…It can be applied to study the chemical environment around the atoms of various elements in electrode materials and to obtain important information about the oxidation state, local structure, and proximity of coordination atoms of the constituent elements in electrode materials. 45,[77][78][79][80] According to the energy range of X-ray photons, they can be divided into soft XAS (sXAS) and hard XAS (hXAS), where sXAS tests X-ray photons with low energy and weak penetration and can be used to study the energy state of superficial elements (K-plane of C, O, N, etc. and L-plane of most transition metals), while hXAS has high energy and strong penetration and can be used to study the energy state of physical phase elements (K-plane of most transition and K-plane of most transition metals) in terms of energy states, atomic occupation, local environment, and other information.…”
Section: X-ray Absorption Spectroscopy (Xas)mentioning
confidence: 99%
“…The increase in capacity can be achieved not only by doping electroactive TMs (Ni, Fe, Cu, and Co) in Na x MnO 2 but also by using electro-inactive doping, such as Li, [20][21][22] Mg, [23][24][25] and Zn [26,27] or even vacancies □. [28,29] This type of doping leads to the Na-O-A configuration (A = Li, Mg, Zn, □) and causes the formation of oxygen lone-pair states, which activates oxygenredox reactions.…”
Section: Introductionmentioning
confidence: 99%
“…However, most of these binary systems with A = Li, Mg, and Zn suffer from low operation voltage and large voltage hysteresis between charge and discharge. [20][21][22][23][24][25][26][27] A survey of the literature reveals that it may be related to Li migration from the TM to Na layer and the rearrangement of Mn in the TM layer. [22] For example, Bruce et al [22] showed that the in-plane Li/Mn rearrangement in Na x [Li y Mn 1−y ]O 2 materials can be reduced by the formation of a Li/Mn ribbon superstructure with less in-plane reordering than in the Li/Mn honeycomb superstructure.…”
Section: Introductionmentioning
confidence: 99%
“…2 Oxygen redox has been reported in the Na-deficient Mn-based layered oxide cathode materials for the sodium-ion batteries (SIBs) and results in specific capacities up to >200 mA h g −1 . 3–5…”
mentioning
confidence: 99%